Penerapan Media Papan Perkalian pada Pembelajaran Matematika di Kelas IV Sekolah Dasar Melalui Kegiatan Pengabdian Masyarakat UINSU - Fitri Harabiyah Gultom; Nabilah Azrilia Marpaung; Fathiyah Rahma Hamali Zega; Riana Riana (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to determine the effect of the application of multiplication board media in mathematics learning on students' understanding of multiplication concepts in grade IV of elementary school. This study uses a qualitative approach with a descriptive method conducted in several elementary schools. Data were collected through observation, interviews with teachers and students, and documentation of learning activities. The results of the study indicate that the use of multiplication board media can improve students' understanding of multiplication concepts. Students who initially had difficulty memorizing multiplication tables showed significant progress after using this media, as seen from their ability to work on multiplication problems faster and more accurately. In addition, the use of this media also increased student involvement and motivation in learning. Teachers reported that the multiplication board media made it easier for them to explain multiplication concepts in a more concrete and visual way, and increased student participation in class. Based on these results, it can be concluded that the application of multiplication board media in mathematics learning can be an effective alternative to improve students' understanding of multiplication material. This media not only makes mathematics learning more interesting, but also strengthens the basic concepts of mathematics taught in elementary school.